Evaluation of specific speed and endurance preconditions of white-water canoeists - Süss, V.; Bily, M.; Bunc, V. (International Journal of Fitness, 2008)
Evaluation of preconditions for sport performance is the basic premise of successful training process. One of the possibilities is the evaluation on the basis of muscle biopsy that is measuring morphological structure of decisive muscle groups. However, using invasive methods for these purposes is very limited today.